Immobilization of Eu and Ho from synthetic acid mine drainage by precipitation with Fe and Al (hydr)oxides - Barcelos, Gisely S.; Veloso, Renato Welmer; Mello, Jaime W. V. de; Gasparon, Massimo (Environmental Science and Pollution Research, 2018)
Use of lime to mitigate acid mine drainage is, in general, accompanied by precipitation of iron (Fe) and aluminium (Al) (hydr)oxides which may increase the removal of trace elements from water. This work aimed to evaluate the precipitation of Fe/Al (hydr)oxides to remove rare earth elements (REE) from contaminated water and the stability of precipitates. Two sets of 60-day syntheses were carried out using different Fe/Al/REE molar ratios, for europium (Eu) and holmium (Ho). The pH was periodically adjusted to 9.0, and the stability of the resulting precipitates was evaluated by water-soluble and BCR extractable phases, namely (1) acid soluble, extracted by 0.11 mol L−1 acetic acid; (2) reducible, extracted with 0.5 mol L−1 hydroxylamine hydrochloride; and (3) oxidisable, extracted with 8.8 mol L−1 hydrogen peroxide efficiencies of the water treatments for both Eu and Ho that were higher than 99.9% irrespective to the Fe/Al/REE molar ratios. Water-soluble phases of Eu and Ho were lower than 0.01% of the total contents in the precipitates. Recoveries from precipitates by Bureau Communautaire de Référence (BCR) sequential extractions increased with increasing concentrations of Eu and Ho. Acetic acid extracted higher amounts of REE, but Eu recovery was superior to Ho. Lepidocrocite was formed as Eu concentration increased which decreased its stability in the precipitates.
Keywords: Rare earth elements; Oxides; Acid mine drainage; Wastewater; Sorption; Co-precipitation